Assessing the Accessibility and Utilization of Agricultural Credit Facilities in Ruhinda Sub-County Rukungiri District. - Tukahirwa, Horus (Kabale University, 2025)
This study assessed the accessibility and utilization of agricultural credit facilities in Ruhinda Sub County, Rukungiri District. The objectives were to evaluate the level of awareness among farmers regarding these facilities, identify the barriers hindering access, and examine the impact of agricultural credit on farm productivity. The research adopted a descriptive design, utilizing a multistage sampling technique to select participants. Initially, the study area was divided into clusters, followed by random sampling to choose specific villages within each cluster. Systematic random sampling was employed to select households for farmer interviews, while community leaders were purposively selected based on their positions and knowledge of community affairs. Data were collected using questionnaires for farmers, which included both closed-ended and open-ended questions, and interview guides for community leaders to facilitate in-depth discussions. The findings revealed that 70% of farmers were aware of agricultural credit facilities, with government-sponsored programs being the most recognized. However, significant barriers such as high interest rates, lack of collateral, and complex application procedures hindered access to these credits. The study also found that agricultural credit positively impacted farm productivity, with increased crop yields and expanded farm sizes reported by 78% and 57% of respondents, respectively. Despite this, overall satisfaction with the credit facilities was moderate, indicating a need for improvement in service delivery. The study concluded that while awareness of agricultural credit facilities was relatively high, barriers significantly limited access and utilization. Recommendations included reducing interest rates, simplifying application procedures, and increasing targeted awareness campaigns to enhance farmers' access to credit and improve overall satisfaction.